Sugammadex for the reversal of muscle relaxation in general anaesthesia: A systematic review and economic assessment. - Soren, Sasmita; Tirkey, Manisha; Baskey, Shyam Charan (Student's Journal of Health Research Africa, 2025)
Background For intubation and surgical optimisation, general anaesthesia requires neuromuscular blocking agents (NMBAs). Sugammadex, a new reversal drug, reverses Aminosteroidal-induced neuromuscular blockade quickly and predictably, improving patient outcomes and operating room efficiency. Objectives To evaluate the clinical effectiveness and economic viability of sugammadex compared to neostigmine or placebo for the reversal of rocuronium- or vecuronium-induced neuromuscular blockade in general anaesthesia. Methods A comprehensive review compared sugammadex to neostigmine or placebo for reversing moderate, profound, and acute neuromuscular blockade. Recovery timeframes, safety, and economic impacts were collected. A de novo cost-effectiveness model based on UK NHS practice assessed the value per minute of recuperation time saved. Results Sugammadex shortened recovery times by 1.3–1.7 minutes (moderate blockade) and 2.7 minutes (deep blockade) compared to neostigmine and placebo. Economic studies showed that sugammadex might be cost-effective if operating room recovery time savings were over £2.40 per minute. The safety profile was better than neostigmine. Conclusion Sugammadex is a clinically effective and potentially cost-efficient agent for NMB reversal. Its advantages are especially relevant in high-turnover or high-risk surgical settings, though broader economic assessments across healthcare systems are needed.